Modeling of Direct Steam Generation in Concentrating Solar Power Plants. (November 2016) - Ravelli, S.; Franchini, G.; Perdichizzi, A.; Rinaldi, S.; Valcarenghi, V.E.
Abstract: A simulation procedure has been developed to predict the performance of a concentrating solar power plant with direct steam generation (DSG) technology. A detailed modelling of the DSG solar field was conceived for both parabolic troughs (PTC) and linear Fresnel collectors within an integrated Octave-TRNSYS® environment. Predictions from this model were compared with published operational data of the first pre-commercial 5 MW DSG solar power plant, designed within the INDITEP project. Attention was paid to the plant performance under two different operation modes, i.e. "fixed" or "sliding" steam turbine inlet pressure.